2010
DOI: 10.1007/s11998-010-9288-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of phosphate–alumina pigments in waterborne paints for protection of cold-rolled steel

Abstract: Core-shell theory presents a new easy method to obtain high performance, economic, and eco-friendly anticorrosive mixed pigments. The coreshell pigments in this work are prepared by depositing a surface layer of an expensive efficient anticorrosive pigment (phosphates) on a bulk of less expensive extender pigment (alumina). The combination of these two compounds led to the production of new pigments with improved properties different from each of its individual components; and consequently these improved prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Generally, electrochemical studies were in high accordance with accelerated laboratory test results which revealed that group IV was the best and paint films containing TiO 2 /SiO 2 (3) showed the best corrosion inhibition behaviour among all paint films of the groups.…”
Section: Groupsupporting
confidence: 70%
See 1 more Smart Citation
“…Generally, electrochemical studies were in high accordance with accelerated laboratory test results which revealed that group IV was the best and paint films containing TiO 2 /SiO 2 (3) showed the best corrosion inhibition behaviour among all paint films of the groups.…”
Section: Groupsupporting
confidence: 70%
“…The presence of shell can alter some properties of core like surface charge, functionality and reactivity. These new core-shell particles are widely applied in different applications [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These modifications have led to better water solubility, good corrosion protection in addition to being eco-friendly (Naderi et al , 2014). Core-shell method is introduced for the preparation of new advanced materials (Ahmed, 2009; Ahmed and Mohamed, 2011). Core-shell materials were promoted with the idea of gathering two components in one compound to help in overcoming the defects of the individual components by gaining new properties and gathering the properties of both components, so that they can offer different new possibilities and innumerable combinations.…”
Section: Introductionmentioning
confidence: 99%
“…The core-shell theory is a new way of obtaining high performance, and eco-friendly extender pigments that are cost-effective. In this theory, a cheap extender being the core is covered by a surface layer of very efficient and expensive pigment-the shell [2]. Core-shell particles are examples of nanostructured materials with functional properties such as composite materials where the morphology, microstructure and chemical composition are controlled to achieve various functional properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these methods are difficult to replicate in commercial quantity because of the multiple steps, pH control, ingredients like surfactant polyelectrolytes and cutting-edge technologies required [3]. Many literature sources have revealed excellent report on the preparation of core-shell extender pigments [2] [18].…”
Section: Introductionmentioning
confidence: 99%